A positive psychology perspective on pre-deployment fitness-for-duty evaluations for external deployments: A proposition for the South African National Defence Force - Bester, Piet (Scientia Militaria - South African Journal of Military Studies, 2022)
The aim of this article is to introduce the reader to a psychological well-being orientation for soldiers in pre-deployment fitness-for-duty evaluations by screening for psychological risk rather than pathology. The aim is reached by firstly discussing the existing process of pre-deployment fitness-for-duty evaluations, then conceptualising the assessment for psychological risk rather than psychopathology only, followed by linking pre-deployment assessment of fitness-for-duty evaluations to the positive psychology paradigm and proposing an integrative military model for soldiers’ psychological well-being in the external deployment context. The discussion is concluded by recommendations for military decision-makers to consider this approach of psychological risk assessment as a feasible process.